UNVEILING EMOTIONS: A COMPREHENSIVE EXPLORATION OF ANALYZING, UNDERSTANDING, AND MANAGING EMOTIONAL RESPONSES - Ibragimov , Sherzod; Rayimjanova , Kamilla; Ganieva , Aziza; Normakhmadov , Shohjakhon; Kobilova , Zarina (Collection of scientific papers «ΛΌГOΣ», 2023)
Emotions are intricate facets of human experience, influencing cognition, behavior, and overall well-being. This comprehensive article aims to explore the diverse dimensions of emotions within the framework of psychology. Delving into various psychological theories, assessment techniques, neurobiological underpinnings, cultural influences, clinical applications, and future directions, this paper provides an in-depth understanding of emotional analysis and regulation. By examining the multidisciplinary aspects of emotions, it aims to offer valuable insights for fostering emotional intelligence and well-being.